Arginine methylation and ubiquitylation crosstalk controls DNA end-resection and homologous recombination repair - Maria Pilar Sanchez-Bailon (Nature Portfolio, 2021)
Post-translational modifications are critical for regulating the DNA damage response. Here, the authors identify a methylation-deubiquitination crosstalk between methyltransferase PRMT1 and deubiquitinase USP11, showing that the enzymes regulate each other’s functions in DNA repair.